Transformações em curso: o avanço do meio técnico-científico informacional na região metropolitana de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
This work is looking for to insert itself in debate of new socio-spatial practices that develop in the Western Amazon, as a result of the metropolitan phenomenon that was made possible the institutionalization of the Metropolitan Region of Manaus/RMM, in 2007, and was intensified after the inauguration of the Jornalista Phelippe Daou bridge (Manaus-Iranduba), in 2011. The inauguration of the aforementioned bridge allowed the expansion and intensification of the metropolization of space with greater fluidity and reach, starting from the metropolis Manaus, mainly towards the municipalities accessed by the highway axis AM-070. In practice, this process favored the emergence of new socio-spatial practices in the municipalities belonging to the regional unit, such as the expansion of the real estate sector, a significant increase in vehicles and enterprises that were previously only seen in the metropolis. As well as the exponential increase in numbers of access to telecommunication systems, allowing the development of new ways of carrying out life in the regional context. The objective of this work was understand the structural conformation of mobile and fixed telecommunication networks in four cities of RMM, namely, Iranduba, Manacapuru, Careiro da Várzea and Careiro. More specifically, it was sought to analyze the dynamics of internet access networks in each municipality and identify the main structures that subsidize the operation of flows in the study area, especially in geographic aspect. The research process included procedures and techniques such as survey and literature review, field work, colect and systematization of primary and secondary data in databases, tables, charts, graphs and maps, and writing, parallel to the dissertation review. Finally, this work is structured in three major chapters, namely, the first one where the methodological issues and the conceptual/theoretical assumptions of the research were discussed; a second one where the dynamics of internet access networks was analyzed in a historical series that goes from 2007 to 2021 and elements that pointed to these ongoing transformations were identified in urban landscapes of study area. Finally, there is a third chapter responsible for identifying the most important structures that subsidize flows of internet access in RMM, considering its spatial rather than technical aspect.
Ongoing transformations
Keywords: Manaus, Região Metropolitana de (AM) - Geografia; Acesso à Internet - Manaus, Região Metropolitana de (AM); Telecomunicações; CIENCIAS HUMANAS: GEOGRAFIA; Metropolização do espaço; Amazônia ocidental; Região metropolitana de Manaus; Meio técnico-científico informacional